Determinant Analysis of Stock Return in LQ45 Company - Kusmayadi, Dedi; Firmansyah, Irman; Rustendi, Tedi (International Journal of Psychosocial Rehabilitation, 2020)
LQ45 Company is a company that has the highest stock liquidity on the Indonesia Stock Exchange. The index is selected every 6 months so that every 6 months companies that cannot maintain their liquidity will be delisted from the group of 45 blue-chip companies. This study aims to analyze the effect of firm size, debt to equity ratio and return on assets on stock returns in companies listed in the sector. The sampling technique used was purposive with the companies criteria that were recorded for more than 6 periods during 2013-2018, so that 19 companies were obtained. By using multiple regression analysis, the results of the study show that stock returns in this sector are not influenced by assets owned so assets are not strong enough to predict stock returns. Investors are actually more interested in using the debt to equity ratio and return on assets as predictors of stock returns. This study shows that debt to equity ratio has a positive effect on stock returns, while return on assets has a negative effect on stock returns on companies listed in LQ45.